Detection vision development in infants and toddlers with congenital vision disorders and profound‐severe visual impairment. (1st April 2020) - Salt, Alison T; O'Reilly, Michelle A; Sakkalou, Elena; Dale, Naomi J
Abstract : Aim: To investigate detection vision development in infants and toddlers with congenital disorders of the peripheral visual system (CDPVS) and severe to profound visual impairment (SVI/PVI). Method: This was a longitudinal observational investigation of a cohort of infants with CDPVS (entry age 8–16mo) followed up 12 months later. Detection vision (Near Detection Scale [NDS]) and resolution acuity (Keeler Acuity Cards [KAC]) were assessed at each time point. Relationships between detection vision, resolution acuity, and age were investigated. Results: The study cohort comprised 80 children (39 females, 41 males), mean age 13 months (Time 1) and 26 months (Time 2); 22 (27.5%) with PVI (light perception at best) and 58 (72.5%) with SVI (basic 'form' vision) at Time 1. All children achieved a measure with the NDS, however only 35 per cent and 56 per cent at Time 1 and Time 2 respectively did so on KAC. Those with PVI at Time 1 showed no further improvement at Time 2, but 87 per cent of children with SVI showed improvement in vision. The median change in NDS score was 1.0 (range 1–7, SD 1.68). Interpretation: Vision development continues after 12 months of age in many toddlers if they have basic 'form' vision. A measure of detection vision is feasible in very young children when resolution acuity measurement is not achievable. What this paper adds: The Near Detection Scale (NDS) can measure low levels of vision when acuity is not otherwise measurable. Vision can improve in toddlers with severe visual impairment who have some 'form' vision. Infants with light perception at best by 12 months are unlikely to show improvement in vision. There is a moderate negative relationship between the NDS and resolution acuity results. What this paper adds: The Near Detection Scale (NDS) can measure low levels of vision when acuity is not otherwise measurable. Vision can improve in toddlers with severe visual impairment who have some 'form' vision. Infants with light perception at best by 12 months are unlikely to show improvement in vision. There is a moderate negative relationship between the NDS and resolution acuity results.